Macrophagic AMPKα1 orchestrates regenerative inflammation induced by glucocorticoids. (15th December 2022) - Caratti, Giorgio; Desgeorges, Thibaut; Juban, Gaëtan; Stifel, Ulrich; Fessard, Aurélie; Koenen, Mascha; Caratti, Bozhena; Théret, Marine; Skurk, Carsten; Chazaud, Bénédicte; Tuckermann, Jan P; Mounier, Rémi
Abstract: Macrophages are key cells after tissue damage since they mediate both acute inflammatory phase and regenerative inflammation by shifting from pro‐inflammatory to restorative cells. Glucocorticoids (GCs) are the most potent anti‐inflammatory hormone in clinical use, still their actions on macrophages are not fully understood. We show that the metabolic sensor AMP‐activated protein kinase (AMPK) is required for GCs to induce restorative macrophages. GC Dexamethasone activates AMPK in macrophages and GC receptor (GR) phosphorylation is decreased in AMPK‐deficient macrophages. Loss of AMPK in macrophages abrogates the GC‐induced acquisition of their repair phenotype and impairs GC‐induced resolution of inflammation in vivo during post‐injury muscle regeneration and acute lung injury. Mechanistically, two categories of genes are impacted by GC treatment in macrophages. Firstly, canonical cytokine regulation by GCs is not affected by AMPK loss. Secondly, AMPK‐dependent GC‐induced genes required for the phenotypic transition of macrophages are co‐regulated by the transcription factor FOXO3, an AMPK substrate. Thus, beyond cytokine regulation, GR requires AMPK‐FOXO3 for immunomodulatory actions in macrophages, linking their metabolic status to transcriptional control in regenerative inflammation. Synopsis: Macrophages regulate the resolution of inflammation after tissue damage. The metabolic sensor AMP‐activated protein kinase and the transcription factor FOXO3 are required for glucocorticoids to induce restorative macrophages. Glucocorticoids (GC) activate the metabolic sensor AMPK in macrophages. Loss of AMPK abrogates the GC‐induced acquisition of macrophage repair phenotype in vitro and in vivo . AMPK‐dependent GC‐induced genes are co‐regulated by the transcription factor FOXO3, an AMPK substrate. Beyond cytokine regulation, the glucocorticoid receptor requires AMPK‐FOXO3 for the control of regenerative inflammation. Abstract : Macrophages regulate the resolution of inflammation after tissue damage. The metabolic sensor AMP‐activated protein kinase and the transcription factor FOXO3 are required for glucocorticoids to induce restorative macrophages.